Study on Energy Consumption Characteristics of Different Tools under Impact Load - Fujun Zhao; Haifan Wang; Zhouyuan Ye; Yonghong Liu; Yu Li (Advances in Civil Engineering)
Three different tools for rock breaking were designed and fabricated. Impact crushing tests were conducted on granite samples with an identical impact velocity by using the variable section Split Hopkinson pressure bar (SHPB) test device. In the test, the incident energy, absorbed energy, and cumulative energy values of acoustic emission during the process of rock breaking were collected, and energy utilization efficiency was used as a measure of the energy consumption characteristics for three different tools breaking rock. Experimental results showed that the cruciform tool has the best performance with respect to the energy utilization efficiency, followed by the one-shaped tool and the spherical tool. The cumulative energy values of the acoustic emission of different tools follow the same regularity.